ISOLATION AND CHARACTERIZATION OF MULTI-DRUG RESISTANCE PROTEUS VULGARIS FROM CLINICAL SAMPLES OF UTI INFECTED PATIENTS FROM MIDNAPORE, WEST BENGAL: Life Sciences-Microbiology - DEBASIS MANDAL; SANDEEP KUMAR DASH; BALARAM DAS; SOMENATH ROY; MANIDEEPA SENGUPTA; PRATIP KUMAR KUNDU (International Journal of Life Science and Pharma Research, 2022)
Recent global concern is that the inappropriate treatment and misuse of antibiotics leads to the emergence of antibacterial multidrug resistance in Proteus vulgaris and others common pathogenic bacteria. The present study investigates the prevalence of antibiotic resistance among Proteus vulgaris bacterial isolates from urine samples of UTI infected hospitalized patients. Thirty six (36) strains of Proteus vulgaris were collected from twelve hundred sixty (1260) Urinary Tract Infected (UTI) urine samples of the patients admitted to the nearby District Hospital. Characterization of isolated strains was determined by biochemical tests. Sensitivity pattern of isolates were determined by some standard antibiotics. From this study, it was revealed that 59.53% isolates were gram’s negative. Indole positivity was observed for 94.44% of Gram’s negative strains. Isolated strains were 100% positive for methyl red, urease, Phenylalanine deaminase, nitrate reduction, motility, Acid production on D-Glucose, D-sorbitol, Rafinose. 94.44% positivity was seen in urease and gilatinase test. H2S production seen in 97.22% on Triple Sugar Iron (TSI) agar test respectively. 100% negativity was seen for Voges-Proskaue, Oxidase, Lactose (MacConkey agar), Citrate and Glycerol (Acid production) test. It was also observed that isolates were non lactose fermented on differential media such as MacConkey and CLED agar. Antibiotic susceptibility of characterized P. vulgaris strains were 100% multi drug resistant.